Reforming Local Governance through Municipal Mergers: Lessons from Japan for Nepal - Chaudhary, Munni Kumari (Prashasan: The Nepalese Journal of Public Administration, 2025)
Japan has a long history of implementing municipal mergers to reform its local governance system. In Nepal, municipal mergers took place as part of the restructuring of local governments following the implementation of the new constitution in 2015. This paper aims to conduct a comparative analysis of the municipal merger processes in Japan and Nepal, focusing primarily on the reasons behind these mergers, the methodologies employed, and the outcomes observed. The goal is to provide policy recommendations on mergers to improve local governance in Nepal. The study is based on a comprehensive literature review and comparative analysis. It involves reviewing both theoretical and empirical literature to offer an overview of the municipal merger approach, along with global trends and practices. The analysis of municipal mergers in Japan and Nepal reveals that Nepal’s mergers were constitutionally mandated and top-down, designed to establish local governments within a federal structure. In contrast, Japan’s mergers were voluntary, driven by demographic and financial crises. Despite significantly reducing the number of local governments, Nepal's process faced political biases, raising concerns about the long-term viability of its local governments. Given the problems and challenges that Nepal’s existing local governments have begun to face, this paper argues that Nepal can improve local governance through municipal mergers. Regular reforms, voluntary mergers with fiscal incentives, and building trust among all levels of government are recommended for the successful amalgamation of local governments in Nepal.